Copper-chromium-niobium alloy, preparation method and vacuum arc-extinguishing chamber

A copper-chromium-niobium alloy, prepared via gradient heating and advanced processing techniques, addresses the deformation issues of existing vacuum arc extinguishing chambers, improving mechanical properties and electrical conductivity for enhanced chamber performance.

CN119242982AInactive Publication Date: 2025-01-03SHAANXI SIRUI ADVANCED MATERIALS CO LTD

Patent Information

Application Number
CN202411784740.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-01-03
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing vacuum arc extinguishing chambers using oxygen-free copper and CuCr materials suffer from significant strength reduction during high-temperature brazing, leading to deformation and reduced service life due to increased arc energy and opening forces at higher voltage levels, necessitating improved mechanical properties and electrical conductivity.

Method used

A copper-chromium-niobium alloy is developed through a method involving gradient heating, vacuum atomization, cold and hot isostatic pressing, and hot extrusion to enhance mechanical properties and electrical conductivity, reducing deformation and improving material utilization.

Benefits of technology

The copper-chromium-niobium alloy exhibits improved mechanical properties and electrical conductivity, reducing deformation and extending the service life of vacuum arc extinguishing chambers by enhancing material utilization and reducing production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119242982A_ABST
    Figure CN119242982A_ABST
Patent Text Reader

Abstract

The invention discloses a copper-chromium-niobium alloy, a preparation method and a vacuum arc extinguish chamber, and the preparation method comprises the following steps: heating and melting a chromium block and a niobium block to prepare a Cr2Nb intermediate alloy; the Cr2Nb intermediate alloy and a copper bar are smelted, so that Cu4Cr2Nb alloy liquid is obtained; the Cu4Cr2Nb alloy liquid is subjected to atomization powder preparation, so that Cu4Cr2Nb alloy powder is obtained; the Cu4Cr2Nb alloy powder is subjected to cold isostatic pressing, so that a Cu4Cr2Nb alloy bar material is obtained; the Cu4Cr2Nb alloy bar is subjected to hot isostatic pressing, so that a Cu4Cr2Nb alloy ingot is obtained; the Cu4Cr2Nb alloy ingot is subjected to hot extrusion, so that a Cu4Cr2Nb alloy ingot blank is obtained; and the Cu4Cr2Nb alloy ingot blank is machined, so that the copper-chromium-niobium alloy is obtained. Various properties of the copper-chromium-niobium alloy can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of materials science and metallurgical engineering, and specifically relates to a copper-chromium-niobium alloy, a preparation method and a vacuum arc extinguishing chamber. Background Art

[0002] As global concern about climate change increases, it is required to replace SF with vacuum switches at 72.5kV, 126kV, and 252kV voltage levels. 6 switch to reduce SF 6 The impact of greenhouse gases on global warming. With the increase of voltage level, the size of arc extinguishing chamber is also increasing, the opening distance of arc extinguishing chamber during the breaking process is also increasing, the opening and closing force during the breaking process is also increasing, and the arc energy during the breaking process is increased, which puts forward higher requirements on the high temperature softening performance of contact cup material and conductive rod material. The conductive rod and contact cup of the existing vacuum arc extinguishing chamber are mainly made of oxygen-free copper and a small amount of CuCr material. However, during the production process of vacuum arc extinguishing chamber, these two materials are greatly reduced in strength (the reduction is more than 50%) after high temperature (820℃~850℃) vacuum brazing. When used at a high frequency, the dynamic conductive rod will be bent, bulged and other deformation problems, which greatly reduces the service life of the vacuum arc extinguishing chamber and causes serious failures, resulting in the inability to quickly, reliably and safely cut off the power supply. Summary of the invention

[0003] The main purpose of the present application is to provide a copper-chromium-niobium alloy, a preparation method and a vacuum arc extinguishing chamber. The present application can improve the mechanical properties and electrical conductivity of the copper-chromium-niobium alloy.

[0004] A copper-chromium-niobium alloy, the components of the copper-chromium-niobium alloy and the mass percentage of each component are: Cr 3.0-3.5%, Nb 2.2-3.0%, and Cu as the balance.

[0005] The present application also provides a method for preparing a copper-chromium-niobium alloy, the method comprising: heating and melting a chromium block and a niobium block to prepare a Cr2Nb master alloy; smelting the Cr2Nb master alloy and a copper rod to obtain a Cu4Cr2Nb alloy liquid; atomizing and powdering the Cu4Cr2Nb alloy liquid to obtain a Cu4Cr2Nb alloy powder; cold isostatic pressing the Cu4Cr2Nb alloy powder to obtain a Cu4Cr2Nb alloy bar; hot isostatic pressing the Cu4Cr2Nb alloy bar to obtain a Cu4Cr2Nb alloy ingot; hot extruding the Cu4Cr2Nb alloy ingot to obtain a Cu4Cr2Nb alloy ingot blank; and machining the Cu4Cr2Nb alloy ingot blank to obtain a copper-chromium-niobium alloy.

[0006] Optionally, the mass percentage of the Cr2Nb master alloy is 2-7%.

[0007] Optionally, the chromium block and the niobium block are heated and melted by gradient heating.

[0008] Optionally, the Cr2Nb master alloy and the copper rod are melted at a temperature of 1800-1900°C.

[0009] Optionally, the pressure for cold isostatic pressing of the Cu4Cr2Nb alloy powder is set to 150-300 MPa, and the holding time is set to 7-10 min.

[0010] Optionally, the Cu4Cr2Nb alloy rod is subjected to hot isostatic pressing to obtain a Cu4Cr2Nb alloy ingot, comprising: wrapping the Cu4Cr2Nb alloy rod with a steel sleeve to form a sleeve; heating the sleeve, and degassing the sleeve after heating; after degassing, sealing the sleeve, sintering the sealed sleeve, and obtaining the Cu4Cr2Nb alloy ingot after pressure-maintaining cooling.

[0011] Optionally, the heating temperature for heating the package is 500~600℃.

[0012] Optionally, the Cu4Cr2Nb alloy ingot is hot extruded at a temperature of 800-950°C.

[0013] In addition, the present application also provides a vacuum interrupter, which includes a contact, and the contact is made of a copper-chromium-niobium alloy, and the copper-chromium-niobium alloy is prepared by a copper-chromium-niobium alloy preparation method as described in any of the preceding items.

[0014] Compared with the prior art, the present application can bring the following beneficial effects: the present application adopts alloy powder to be first cold isostatically pressed and then hot isostatically pressed to obtain copper-chromium-niobium alloy rods. Compared with directly encapsulating the copper-chromium-niobium alloy powder and then hot isostatically pressed, the deformation degree of the rods in the hot isostatic degassing process is greatly reduced, and the utilization rate of the material in the processing process is improved; in addition, the rods are further subjected to hot extrusion deformation treatment to obtain a blank shape close to the product size, which further improves the utilization rate of the material in the blank stage, so that the material utilization rate of the product is further improved, and the production cost of the product is greatly reduced. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 It is a schematic flow chart of a method for preparing a copper-chromium-niobium alloy provided in one embodiment of the present application; Figure 2 is a metallographic diagram of a copper-chromium-niobium alloy provided in another embodiment of the present application; Figure 3 This is a metallographic diagram of a copper-chromium-niobium alloy prepared based on an existing method; Figure 4It is a schematic diagram of a hot isostatic pressing blank and a hot extrusion blank provided in another embodiment of the present application. DETAILED DESCRIPTION

[0016] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0017] It should be noted that all directional indications (such as up, down, left, right, front, back, etc.) in the embodiments of the present invention are only used to explain the relative position relationship, movement status, etc. between the components under a certain specific posture (as shown in the accompanying drawings). If the specific posture changes, the directional indication will also change accordingly.

[0018] In the present invention, unless otherwise clearly specified and limited, the terms "connection", "fixation", etc. should be understood in a broad sense. For example, "fixation" can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements, unless otherwise clearly defined. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0019] In addition, if there are descriptions involving "first", "second", etc. in the embodiments of the present invention, the descriptions of "first", "second", etc. are only used for descriptive purposes and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of technical features indicated. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In addition, the meaning of "and / or" appearing in the full text includes three parallel schemes. Taking "A and / or B" as an example, it includes scheme A, or scheme B, or a scheme that satisfies both A and B. In addition, the technical solutions between the various embodiments can be combined with each other, but it must be based on the ability of ordinary technicians in the field to implement. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such a combination of technical solutions does not exist and is not within the scope of protection required by the present invention.

[0020] In an exemplary embodiment, the present application provides a copper-chromium-niobium alloy, wherein the components of the copper-chromium-niobium alloy and the mass percentage of each component are: Cr 3.0-3.5%, Nb 2.2-3.0%, and Cu as the balance.

[0021] In this embodiment, the ratio of the above components is determined by the present application through a series of experimental studies, and the specific determination method is as follows: This application prepares CuCrNb alloy samples with different Cr and Nb contents, and tests each sample for physical and mechanical properties, such as tensile strength, hardness, electrical conductivity, high temperature resistance and corrosion resistance, and uses metallographic microscope and scanning electron microscope (SEM) to observe the microstructure of copper-chromium-niobium alloy. The results show that when the Cr content is 3.0~3.5%, the strength and hardness of the alloy reach the optimal level, while maintaining good ductility and processing properties, and when the Nb content is 2.2~3.0%, the high temperature resistance and creep resistance of the alloy are optimal, while maintaining good electrical conductivity and corrosion resistance. In addition, this application also performs different heat treatment processes on CuCrNb alloy samples with different compositions, such as annealing, quenching and tempering. The results show that within the range of 3.0~3.5% Cr and 2.2~3.0% Nb content, the copper-chromium-niobium alloy has the best performance after proper heat treatment.

[0022] Furthermore, the present application also uses thermodynamic software (such as FactSage) to calculate the thermodynamic parameters of CuCrNb alloys with different compositions during the smelting and solidification processes, such as free energy, activity, etc., and uses a kinetic model (such as the Johnson-Mehl-Avrami-Kolmogorov model) to predict the solidification rate and grain size of the alloy. The results show that: within the range of 3.0~3.5% Cr and 2.2~3.0% Nb content, the solidification rate of the alloy is moderate and the grain size is uniform, which is beneficial to improving the comprehensive performance of the copper-chromium-niobium alloy.

[0023] In another exemplary embodiment, the present application also provides a method for preparing a copper-chromium-niobium alloy, such as Figure 1 As shown, the preparation method comprises the following steps: S1: Preparation of chromium-niobium (Cr2Nb) master alloy; In this step, chromium blocks (Cr) and niobium blocks (Nb) are placed in a crucible, and then the crucible is placed in a vacuum melting furnace. The vacuum pump is started to evacuate the furnace to 1*10 -2Pa, to ensure that impurities and oxides are avoided during the smelting process. Then turn on the electromagnetic inductor, and generate eddy currents on the metal raw materials (Cr and Nb) through the electromagnetic field. The heat generated by the eddy currents gradually heats up the metal raw materials until they melt. In this process, the electromagnetic inductor adopts a gradient heating method. First, adjust the power of the electromagnetic inductor to 25kW, and keep it warm for 3 minutes at this power to preliminarily heat the Cr block and Nb block. Then, adjust the power to 50kW, and keep it warm for 3 minutes at this power to further increase the temperature so that the metal raw materials begin to melt. Finally, adjust the power to 70kW and keep it at this power for 1 minute to ensure that the Cr block and Nb block are completely melted. After the Cr block and Nb block are completely melted, adjust the power of the electromagnetic inductor to 10kV, turn off the heating source, and pour the molten metal into the mold for casting. Fill argon gas during the casting process, and obtain the chromium-niobium (Cr2Nb) master alloy after cooling.

[0024] It should be noted that in the process of preparing chromium-niobium (Cr2Nb) master alloy, the reason why the chromium block (Cr) and niobium block (Nb) are heated in a gradient manner is that: first, the gradient heating can reduce the thermal stress caused by the temperature difference inside the chromium block (Cr) and niobium block (Nb), avoid cracks or other damage caused by sudden temperature change, and thus improve the quality of the master alloy; if the temperature is directly increased rapidly, due to the large temperature difference between the inside and outside of the chromium block (Cr) and niobium block (Nb), it is easy to cause thermal stress concentration, which will cause cracks inside or on the surface of the chromium block (Cr) and niobium block (Nb), which will not only affect the integrity of the master alloy, but also reduce the mechanical properties of the master alloy. Second, by gradually increasing the temperature, the two elements of chromium (Cr) and niobium (Nb) can be better fully fused, avoiding local overheating and causing component segregation, and ensuring the uniform composition of the master alloy; if the temperature is directly increased rapidly, it will cause local overheating, causing the metal in some areas to melt in advance, while other areas have not yet reached the melting point, resulting in uneven distribution of the composition of the master alloy. Third, the gradient heating can remove the adsorbed gas and impurities on the surface of the material at a lower temperature, reduce the chance of the material contacting the air during the smelting process, and reduce the risk of oxidation and contamination; if the temperature is raised directly and quickly, the adsorbed gas and impurities on the surface of the chromium block (Cr) and niobium block (Nb) will be melted by high temperature before they can escape, and these impurities will be mixed into the melt, affecting the purity of the alloy. In summary, the use of gradient heating can not only improve the stability and controllability of the Cr2Nb intermediate preparation process, but also significantly improve the quality and performance of the alloy. Therefore, when preparing Cr2Nb intermediate alloys, gradient heating is a more scientific and reasonable choice than direct rapid heating.

[0025] S2: adding 2% by mass of a chromium-niobium (Cr2Nb) master alloy and a copper rod (the remainder) into a crucible of a vacuum induction gas atomization device, and smelting them according to the method of step S1 to allow the chromium-niobium (Cr2Nb) master alloy and the copper rod to be physically fused to obtain a Cu4Cr2Nb alloy liquid, and pouring the Cu4Cr2Nb alloy liquid into a tundish of a vacuum induction gas atomization device for atomization and powdering to obtain a Cu4Cr2Nb alloy powder; In this step, during the preparation of the Cu4Cr2Nb alloy liquid, an electromagnetic inductor is used to heat the crucible to 1800°C, and an inert gas (such as argon) is introduced to prevent the metal liquid from coming into contact with air and causing an oxidation reaction. In addition, the metal liquid flow under the tundish is dispersed into fine droplets by the blowing effect of the inert gas, and the droplets solidify during the cooling process to finally form Cu4Cr2Nb alloy powder.

[0026] In the preparation process of Cu4Cr2Nb alloy liquid, due to the high melting point of Cu4Cr2Nb alloy, about 1000℃, in order to ensure the good fluidity of the alloy liquid, it is usually necessary to heat it to a temperature far higher than the melting point. After inspection, 1800℃ is a temperature that ensures the good fluidity of the alloy liquid. If the heating temperature is lower than 1800℃, the fluidity of the alloy liquid may be insufficient, resulting in the droplets being difficult to disperse during the atomization process, forming larger particles, thereby affecting the particle size distribution and uniformity of the Cu4Cr2Nb alloy powder. In addition, if the temperature is lower than 1800℃, the cooling rate of the alloy liquid will slow down, resulting in larger particles and uneven particle size distribution, which will affect the performance of the Cu4Cr2Nb alloy powder.

[0027] In summary, 1800°C can be used as the minimum effective heating temperature for heating the tundish in this step.

[0028] S3: pressing the Cu4Cr2Nb alloy powder into Cu4Cr2Nb alloy rods by cold isostatic pressing; In this step, the Cu4Cr2Nb alloy powder needs to be loaded into the rubber sleeve for grinding. Specifically, the grinding method is: mechanically vibrate the rubber sleeve filled with powder for 30 seconds to ensure that the Cu4Cr2Nb alloy powder is evenly distributed in the rubber sleeve to reduce the gap, lay the foundation for the subsequent compaction operation, and improve the filling density of the powder; grind the rubber sleeve filled with powder 8 times to compact the powder and increase the compactness of the powder to create good conditions for the subsequent cold isostatic pressing operation; then cover the rubber sleeve plug, roll the material for 3 minutes to further compact the powder, and then use a steel card to tighten the rubber sleeve mouth to ensure that the rubber sleeve is sealed to prevent powder leakage, and also ensure the uniform distribution of pressure during the cold isostatic pressing process; turn the rubber sleeve head down, and then grind it in the opposite direction 2 times to further improve the density of the powder, especially the powder in the bottom area of ​​the rubber sleeve, to ensure the uniformity and density of the entire powder body. Through the above steps, not only can the density and uniformity of the powder be significantly improved, but also the defects inside the material can be effectively reduced, and the quality and performance of the final product can be improved. After the powdering is completed, the powdered rubber sleeve is placed in a cold isostatic press for compacting. The pressure of the cold isostatic press is set to 150Mpa, and the holding time is 7min. After the holding time is completed, the Cu4Cr2Nb alloy bar can be obtained.

[0029] It should be noted that, according to experiments, when putting the rubber sleeve of the powder into the cold isostatic press for compacting, 150Mpa can be used as the minimum effective pressure. Under this pressure, the density of the powder can be effectively improved, the internal voids can be reduced, and the powder particles can be tightly combined to form a dense rod. However, if the pressure is less than 150Mpa, it will lead to insufficient pressure, which will cause the powders to be not tightly combined, forming more voids, and then reducing the density of the rod. Low-density rods are prone to cracks, fractures and other problems during subsequent processing and use, affecting the mechanical properties of the final product. In addition, the 7-minute holding time is also an appropriate time setting. If the holding time is less than 7 minutes, the pressure is difficult to be fully transmitted in the powder, which will cause the powder particles to be loosely combined and form more voids, thereby reducing the density of the rod.

[0030] S4: preparing the Cu4Cr2Nb alloy ingot by hot isostatic pressing the Cu4Cr2Nb alloy bar; In this step, the Cu4Cr2Nb alloy bar is firstly wrapped with a steel sleeve to form a sleeve (the sleeve treatment can protect the alloy bar from external pollution, and at the same time, in the subsequent high-temperature treatment process, prevent the alloy from contacting with air to produce oxidation reaction, thereby ensuring the purity of the alloy), and is placed in a heat treatment furnace and heated to 500°C (heating the sleeve to 500°C can preheat the Cu4Cr2Nb alloy bar to a temperature suitable for high-temperature degassing, which is conducive to the effective implementation of the subsequent degassing process). Subsequently, the heated sleeve is taken out of the heat treatment furnace and placed in a degassing device, and a vacuum exhaust system is used to perform high-temperature exhaust on the sleeve (high-temperature degassing can effectively remove residual gas in the alloy material, reduce pores and microcracks inside the material, and improve the density and mechanical properties of the material). The degassing time lasts for 8 hours, and when the vacuum degree in the sleeve reaches 1×10 -3 After Pa, the degassing is stopped, and the exhaust port is sealed with argon arc welding. The sealed package is then placed in a hot isostatic pressing furnace chamber at a temperature of 920°C for hot isostatic pressing sintering. After sintering, the pressure is maintained for 3 hours, and the Cu4Cr2Nb alloy ingot can be obtained after cooling. It should be noted that the sintering temperature is set to 920℃, which can ensure that the low melting point components in the Cu4Cr2Nb alloy ingot, such as copper, form a liquid phase. The presence of the liquid phase can promote the diffusion and rearrangement between particles, thereby increasing the sintering density of the Cu4Cr2Nb alloy ingot and enhancing its mechanical properties. If the temperature is greater than 920℃, some elements in the Cu4Cr2Nb alloy (such as niobium and chromium) will volatilize or chemically react at high temperatures, resulting in composition changes, which will affect the chemical stability and mechanical properties of the alloy, resulting in a decrease in the strength, hardness and toughness of the Cu4Cr2Nb alloy ingot. In addition, if the temperature is too high, the atomic diffusion rate will accelerate and the grain growth rate will increase, resulting in coarse grains, which will reduce the strength and toughness of the Cu4Cr2Nb alloy ingot and increase its internal stress, ultimately affecting the mechanical properties of the Cu4Cr2Nb alloy ingot. On the contrary, if the temperature is too low (less than 920°C), the atomic diffusion rate will slow down and the grain growth rate will slow down, which will lead to uneven grain distribution. The uneven grain structure will reduce the strength and toughness of the Cu4Cr2Nb alloy ingot and increase its internal stress, thereby affecting the mechanical properties of the Cu4Cr2Nb alloy ingot.

[0031] S5: hot extruding the Cu4Cr2Nb alloy ingot to obtain a Cu4Cr2Nb alloy ingot blank close to the product size.

[0032] In this step, the Cu4Cr2Nb alloy ingot needs to be taken out of the steel sleeve and the sleeve removed, and the Cu4Cr2Nb alloy ingot after the sleeve is removed is sawed to a height close to the finished product (the Cu4Cr2Nb alloy ingot is sawed to a height close to the finished product, which can reduce the margin of subsequent processing, improve material utilization, and reduce production costs), and then the sawed Cu4Cr2Nb alloy ingot is loaded into a mold placed in a hot extrusion furnace, and the hot extrusion furnace is heated to 800°C by a resistance furnace, and the hot extruder is started to hot extrude the Cu4Cr2Nb alloy ingot so that the Cu4Cr2Nb alloy ingot undergoes plastic deformation and is extruded through the inner cavity of the mold, thereby forming a Cu4Cr2Nb alloy ingot blank. It should be noted that during the hot extrusion process, the design size of the inner cavity of the mold should be close to the outer dimensions of the finished product, but 1 mm larger than the outer dimensions of the finished product (an appropriate margin can be left during the hot extrusion process) to ensure the dimensional accuracy of the final product.

[0033] S6: Grinding the surface of the Cu4Cr2Nb alloy ingot blank with a grinding wheel or a grinder to remove the oxide scale, burrs and uneven parts on the surface, and then machining the outer circle, plane, hole and other parts of the Cu4Cr2Nb alloy ingot blank with a lathe, a milling machine, a drilling machine and other equipment to ensure that the size and shape meet the design requirements; S7: Annealing or quenching the Cu4Cr2Nb alloy ingot blank after machining, and finally fine-machining it. For example, first use a grinder to fine-grind the key parts of the Cu4Cr2Nb alloy ingot blank, and then use a polishing machine to polish the fine-grinded Cu4Cr2Nb alloy ingot blank to obtain the final copper-chromium-niobium alloy.

[0034] In another exemplary embodiment, the present application also provides a method for preparing a CuCrNb material for a high voltage arc extinguishing chamber, such as Figure 1 As shown, the preparation method comprises the following steps: S10: Preparation of chromium-niobium (Cr2Nb) master alloy; Different from the previous embodiment, the mass percentages of the chromium block (Cr) and the niobium block (Nb) in this step are respectively.

[0035] S20: adding 7% by mass of a chromium-niobium (Cr2Nb) master alloy and a copper rod (the balance) into a crucible of a vacuum induction gas atomization device, and smelting them according to the aforementioned method to obtain a Cu4Cr2Nb alloy liquid, and pouring the Cu4Cr2Nb alloy liquid into a tundish of a vacuum induction gas atomization device for atomization and powdering to obtain a Cu4Cr2Nb alloy powder; Different from the previous embodiment, in this step, during the preparation of the Cu4Cr2Nb alloy liquid, an electromagnetic inductor is used to heat the crucible to 1900°C.

[0036] It should be noted that, compared with heating the crucible to 1800°C as described in the previous embodiment, heating the crucible to 1900°C can further increase the fluidity of the alloy liquid, which is more conducive to the uniform dispersion and refinement of the droplets of the alloy liquid during the atomization process. However, after inspection, if the heating temperature is greater than 1900°C, the oxidation reaction of the alloy liquid when it comes into contact with the air will intensify, resulting in more oxides being generated, which will affect the purity and performance of the Cu4Cr2Nb alloy powder. In addition, if the heating temperature is greater than 1900°C, the cooling rate of the alloy liquid will be very fast, causing the droplets to solidify rapidly during the atomization process to form irregular particles, thereby affecting the particle size distribution and uniformity of the Cu4Cr2Nb alloy powder.

[0037] In summary, 1900°C can be used as the maximum effective heating temperature for heating the tundish in this step.

[0038] S30: pressing the Cu4Cr2Nb alloy powder into Cu4Cr2Nb alloy rods by cold isostatic pressing; In this step, the Cu4Cr2Nb alloy powder needs to be loaded into the rubber sleeve and pounded. Specifically, the pounding method is: mechanically vibrate the filled rubber sleeve for 50 seconds to ensure that the Cu4Cr2Nb alloy powder is evenly distributed in the rubber sleeve to reduce gaps, lay a foundation for subsequent compaction operations, and improve the filling density of the powder; pound the rubber sleeve filled with powder 10 times to compact the powder and increase the compactness of the powder to create good conditions for subsequent cold isostatic pressing operations; then cover the rubber sleeve plug and roll the material for 8 minutes to further compact the powder, and then use a steel clip to tighten the rubber sleeve mouth to ensure that the rubber sleeve is sealed to prevent powder leakage, and also to ensure uniform distribution of pressure during cold isostatic pressing; turn the rubber sleeve head downward and pound it in the reverse direction 3 times to further improve the density of the powder, especially the powder in the bottom area of ​​the rubber sleeve, to ensure the uniformity and density of the entire powder body. The powdered rubber sleeve is placed in a cold isostatic press for compaction. The pressure of the cold isostatic press is set to 300 MPa and the holding time is 10 minutes. After the holding time is completed, the Cu4Cr2Nb alloy bar can be obtained.

[0039] It should be noted that, according to experiments, in the process of placing the rubber sleeve of the well-pressed powder into the cold isostatic press for compacting, 300Mpa can be used as the maximum effective pressure. Under this pressure, the density of the powder can be further improved, so that the particles are more densely packed, thereby improving the overall density. In addition, compared with the pressure of 150Mpa applied in the previous embodiment, the pressure of 300Mpa can be more effectively transmitted to every corner of the powder, so that the powder particles are more evenly distributed in the mold cavity, thereby improving the subsequent processing performance of the bar. However, if the pressure is greater than 300Mpa, it will cause excessive internal stress inside the powder, thereby making the bar brittle and reducing its toughness and ductility. In addition, compared with the holding time (7min) set in the previous embodiment, the holding time of 10min can ensure that the pressure is more fully transmitted in the powder, so that the powder particles are more closely combined, and the internal voids are further reduced, thereby further improving the strength and hardness of the bar. In addition, the holding time of 10min helps to further reduce the tiny voids and cracks between the powder particles, thereby improving the uniformity and integrity of the bar. However, if the pressure is maintained for too long (greater than 10 minutes), it will lead to the accumulation of internal stress in the Cu4Cr2Nb alloy powder, which will increase the micro defects inside the bar and further affect the mechanical properties of the bar.

[0040] S40: preparing the Cu4Cr2Nb alloy ingot by hot isostatic pressing the Cu4Cr2Nb alloy bar; In this step, the Cu4Cr2Nb alloy bar is firstly wrapped with a steel sleeve to form a sleeve, and then placed in a heat treatment furnace and heated to 600°C (at this temperature, the bar can be preheated more fully, which helps to make the bar reach a uniform temperature distribution more quickly, thereby further reducing the thermal stress in the subsequent high-temperature treatment process and avoiding cracks and deformation). Then, the heated sleeve is taken out of the heat treatment furnace and placed in a degassing device. The sleeve is degassed at high temperature using a vacuum exhaust system for 20 hours. When the vacuum degree in the sleeve reaches 1×10 -5 After Pa, the degassing is stopped, and the exhaust port is sealed with argon arc welding to ensure the sealing of the sleeve. The sealed sleeve is then placed in a hot isostatic pressing furnace chamber at a temperature of 920°C for hot isostatic pressing sintering. After sintering, the pressure is maintained for 3 hours to obtain a Cu4Cr2Nb alloy ingot. S50: hot extruding the Cu4Cr2Nb alloy ingot to obtain a Cu4Cr2Nb alloy ingot blank close to the product size.

[0041] In this step, the Cu4Cr2Nb alloy ingot needs to be taken out of the steel sleeve and the sleeve removed, and the Cu4Cr2Nb alloy ingot after the sleeve is removed is sawed to a height close to the finished product (the Cu4Cr2Nb alloy ingot is sawed to a height close to the finished product, which can reduce the margin of subsequent processing, improve material utilization, and reduce production costs), and then the sawed Cu4Cr2Nb alloy ingot is loaded into a mold placed in a hot extrusion furnace, and the hot extrusion furnace is heated to 950°C by a resistance furnace, and the hot extruder is started to hot extrude the Cu4Cr2Nb alloy ingot so that the Cu4Cr2Nb alloy ingot undergoes plastic deformation and is extruded through the inner cavity of the mold, thereby forming a Cu4Cr2Nb alloy ingot blank. It should be noted that during the hot extrusion process, the design size of the inner cavity of the mold should be close to the outer dimensions of the finished product, but 1.5 mm larger than the outer dimensions of the finished product (an appropriate margin can be left during the hot extrusion process) to ensure the dimensional accuracy of the final product.

[0042] Compared with the previous embodiment, the design size of the mold cavity is adjusted from 1mm larger than the finished product size to 1.5mm. Firstly, it can better compensate for the shrinkage of the material and ensure that the size of the final product is closer to the design requirements; secondly, the 1.5mm margin can provide more buffer to ensure that even in the case of uneven material flow or slight wear of the mold, the size of the final product can still meet the design requirements.

[0043] S60: grinding the surface of the Cu4Cr2Nb alloy ingot blank using a grinding wheel or a grinder to remove the oxide scale, burrs and uneven parts on the surface, and then machining the outer circle, plane, hole and other parts of the Cu4Cr2Nb alloy ingot blank using a lathe, a milling machine, a drilling machine and other equipment to ensure that the size and shape meet the design requirements; S70: annealing or quenching the Cu4Cr2Nb alloy ingot blank after machining, and finally performing fine machining, for example, first using a grinder to fine-grind the key parts of the Cu4Cr2Nb alloy ingot blank, and then using a polisher to polish the fine-grinded Cu4Cr2Nb alloy ingot blank to obtain the final copper-chromium-niobium alloy.

[0044] In the above embodiment, the heating temperature of the hot extrusion furnace is set between 800 and 950°C during the hot extrusion of the Cu4Cr2Nb alloy ingot, because: within this temperature range, the copper matrix in the Cu4Cr2Nb alloy ingot will partially melt to form a liquid phase, which is conducive to the diffusion and rearrangement between particles, improves the plasticity of the material, and the good plastic deformation ability can ensure that the alloy passes through the die smoothly during the hot extrusion process to form the desired shape and size. If the temperature is greater than 950°C, certain elements (such as niobium and chromium) in the Cu4Cr2Nb alloy ingot will volatilize or chemically react at high temperatures, resulting in changes in composition, which may cause the strength, hardness and toughness of the Cu4Cr2Nb alloy ingot blank to decrease. On the contrary, if the temperature is less than 800°C, the diffusion and bonding speed between the particles in the alloy will slow down, resulting in more voids inside the alloy and insufficient density, and insufficient density will reduce the mechanical properties of the alloy, such as strength, hardness and toughness.

[0045] In summary, in the hot extrusion process, 800~950℃ is a reasonable and effective hot extrusion temperature, which is helpful to prepare high-quality Cu4Cr2Nb alloy ingot blanks and ensure their reliability and safety in high-performance applications such as high-voltage arc extinguishing chambers.

[0046] In the above embodiment, in the process of preparing the Cu4Cr2Nb alloy liquid, the mass percentage of the Cr2Nb master alloy is set between 2% and 7%. The selection of this range is optimized to ensure that the final alloy has the best physical and mechanical properties. If the proportion of the Cr2Nb master alloy is too high (greater than 7%), it will cause excessive growth of grains during the preparation process, forming coarse grains, which will reduce the strength and toughness of the alloy and increase the internal stress of the alloy. After inspection, it will make the final alloy brittle, and the ductility and processing performance will decrease. On the contrary, if the proportion of the Cr2Nb master alloy is too low (less than 2%), it will cause the strength and hardness of the alloy to be insufficient, thereby affecting the processing performance of the alloy.

[0047] In summary, the mass percentage of chromium-niobium (Cr2Nb) master alloy is set at 2~7%, which is a reasonable and effective range, which helps to prepare Cu4Cr2Nb alloy with optimal hardness, strength and conductivity, and ensure its reliability and safety in high-performance applications such as high-voltage arc extinguishing chambers.

[0048] Next, the present application tested the various properties of the CuCrNb alloy prepared by the method described in the present application, and the test results are shown in Table 1: Table 1

[0049] In addition, the present application also tests the various properties of the CuCrNb alloy prepared based on the existing method, and the test results are shown in Table 2: Table 2

[0050] It can be seen from Tables 1 and 2 that the oxygen content and nitrogen content of the alloy prepared by the method described in the present application are lower, indicating that the purity of the alloy is higher; in addition, the electrical conductivity of the alloy prepared by the method described in the present application is higher, indicating that the alloy has better electrical conductivity.

[0051] In summary, by comparing the data in Table 1 and Table 2, it can be seen that the CuCrNb material prepared by the method of the present application shows higher purity in terms of gas content (oxygen content and nitrogen content), and is also slightly better than the material prepared by the existing method in terms of conductivity. These improvements help to improve the overall performance of the material, especially in terms of purity and conductivity, making it more suitable for high-performance applications such as high-voltage arc extinguishing chambers.

[0052] Figure 2 is a metallographic diagram of a CuCrNb alloy prepared by the method described in this application, Figure 2 In the figure, it can be seen that the Cr2Nb2 phase is dispersed in the matrix, which means that the Cr2Nb2 phase is evenly distributed in the entire matrix without obvious aggregation or agglomeration, which can effectively improve the strength and hardness of the alloy while maintaining good plasticity and toughness. In addition, Figure 2 In the Cr2Nb2 phase, the size is in the range of 3~4μm, indicating that the size of the Cr2Nb2 phase is relatively uniform and there is no obvious size difference. Figure 2 It can be seen that after extrusion deformation treatment, the particle boundaries in the alloy become smoother and some particle boundaries have disappeared. This shows that hot extrusion deformation can effectively eliminate some particle boundaries in the alloy, thereby improving the density and mechanical properties of the alloy and reducing potential stress concentration points.

[0053] Figure 3 This is the metallographic diagram of the CuCrNb alloy prepared based on the existing method. Figure 3 In the Cr2Nb2 phase, there is also distribution in the matrix, but there is obviously a certain degree of aggregation and agglomeration. Figure 3 It can be seen that the grain boundaries in the alloy prepared based on the existing method are relatively obvious, and there is no obvious elimination phenomenon, indicating that the existing method has limited effect in eliminating grain boundaries, and the existence of grain boundaries often leads to stress concentration, reducing the fatigue strength and crack growth resistance of the alloy. Furthermore, some tiny holes and defects can be seen in the matrix structure, which will reduce the density of the alloy and affect the strength and corrosion resistance of the alloy.

[0054] In summary, by comparison Figure 2 and Figure 3 It can be seen that the CuCrNb alloy prepared by the method described in this application performs better in terms of phase distribution, particle boundary elimination and uniformity of matrix structure. These improvements help to improve the comprehensive performance of the CuCrNb alloy, especially in terms of strength, hardness, plasticity and toughness, making it more suitable for high-performance applications such as high-voltage arc extinguishing chambers.

[0055] Figure 4 It is a schematic diagram of hot isostatic pressing blank and hot extrusion blank, such as Figure 4 As shown, the present application uses hot extrusion to make the size of the blank close to the size of the final product (such as Figure 4 The hot extrusion method significantly reduces the amount of material removal required for subsequent processing and greatly improves the utilization rate of raw materials. Specifically, the shape and size of the hot extruded blank are very close to the final product, which reduces unnecessary processing allowances, thereby reducing production costs and improving material utilization efficiency.

[0056] On the basis of the above embodiments, the present application further provides a vacuum interrupter, which includes a contact, and the contact is made of a copper-chromium-niobium alloy, and the copper-chromium-niobium alloy is prepared by the preparation method described in any of the above embodiments.

[0057] In a high-voltage vacuum interrupter, the contacts need to withstand high temperatures and high currents. The high-temperature resistance of the CuCrNb alloy prepared by the method described in this application can ensure that the contacts will not deform, wear or break during frequent disconnection, and can reduce the heat generation of the contacts when large currents pass through them, reduce energy consumption, and thus extend the service life of the contacts.

[0058] The above are only preferred embodiments of the present application, and are not intended to limit the patent scope of the present application. Any equivalent structure or equivalent process transformation made using the contents of the present application specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present application.

Claims

1. A copper-chromium-niobium alloy, characterized in that: The components of the copper-chromium-niobium alloy and the mass percentage of each component are: Cr3.0~3.5% Nb2.2~3.0% Cu Residue.

2. A method for preparing a copper-chromium-niobium alloy, characterized in that: The method comprises: The chromium block and the niobium block are heated and melted to prepare a Cr2Nb master alloy; The Cr2Nb master alloy and the copper rod are smelted to obtain a Cu4Cr2Nb alloy liquid; Atomizing the Cu4Cr2Nb alloy liquid to obtain Cu4Cr2Nb alloy powder; cold isostatic pressing the Cu4Cr2Nb alloy powder to obtain a Cu4Cr2Nb alloy bar; Hot isostatic pressing the Cu4Cr2Nb alloy bar to obtain a Cu4Cr2Nb alloy ingot; Hot extruding the Cu4Cr2Nb alloy ingot to obtain a Cu4Cr2Nb alloy ingot blank; The Cu4Cr2Nb alloy ingot blank is machined to obtain a copper-chromium-niobium alloy.

3. The method for preparing a copper-chromium-niobium alloy according to claim 2, characterized in that: The mass percentage of the Cr2Nb master alloy is 2-7%.

4. The method for preparing a copper-chromium-niobium alloy according to claim 2, characterized in that: The chromium block and the niobium block are heated and melted by gradient heating.

5. The method for preparing a copper-chromium-niobium alloy according to claim 2, characterized in that: The Cr2Nb master alloy and the copper rod are melted at a temperature of 1800-1900°C.

6. The method for preparing a copper-chromium-niobium alloy according to claim 2, characterized in that: The pressure of cold isostatic pressing of the Cu4Cr2Nb alloy powder is set to 150-300 MPa, and the holding time is set to 7-10 min.

7. The method for preparing a copper-chromium-niobium alloy according to claim 2, characterized in that: The Cu4Cr2Nb alloy bar is subjected to hot isostatic pressing to obtain a Cu4Cr2Nb alloy ingot, comprising: Wrapping the Cu4Cr2Nb alloy bar with a steel sleeve to form a sleeve; The bag is heated, and after heating is completed, the bag is degassed; After degassing, the package is sealed and welded, and the sealed and welded package is sintered, and the Cu4Cr2Nb alloy ingot is obtained after pressure-maintaining cooling.

8. The method for preparing a copper-chromium-niobium alloy according to claim 6, characterized in that: The heating temperature for heating the package is 500~600℃.

9. The method for preparing a copper-chromium-niobium alloy according to claim 2, characterized in that: The Cu4Cr2Nb alloy ingot is hot extruded at a temperature of 800-950°C.

10. A vacuum interrupter, characterized in that: The vacuum interrupter comprises a contact, and the contact is made of a copper-chromium-niobium alloy, and the copper-chromium-niobium alloy is prepared by a copper-chromium-niobium alloy preparation method according to any one of claims 2 to 9.

Citation Information

Patent Citations

  • Segregation reducing vacuum melting technology of Cu-Cr-Zr alloy cast rod

    CN103938002A

  • Preparation method of high-strength and high-conductivity copper-chromium-niobium conducting rod

    CN118951601A

  • Niobium tin alloy and method for its preparation

    EP3650568A1

Cited By

  • Method for preparing copper-chromium-niobium alloy through mechanical alloying

    CN121204451A